Revisiting the management and epidemiology of common bunt (Tilletia tritici and Tilletia laevis) of wheat in Kansas - De Trinidad, Angel (My University, 2025)
Common bunt (caused by Tilletia tritici and Tilletia laevis) is an economically important disease of wheat, resulting in both yield and grain quality losses. Historically, common bunt has been managed effectively by modern fungicide seed treatments. However, a recent rise in the disease’s prevalence in Kansas has necessitated a reevaluation of current management recommendations. Current recommendations include preventative seed management practices such as purchasing certified seed and applying a fungicide seed treatment, as well as sowing into warmer soil temperatures to avoid infection. To establish a baseline understanding of producer wheat seed management habits and the prevalence of common bunt in Kansas, a survey was disseminated to growers at several K-State Research and Extension events. The survey instrument collected information on grower demographics, common bunt experiences, seed management practices, and extension information preferences. Survey findings report that, while producers frequently purchase certified seed, the overall percentage of their operation planted with certified seed is low, suggesting supplementation of certified seed with other sources such as saved seed. Over half of respondents reported saving a portion of their seed from a previous season, while only approximately a third reported treating that seed with a fungicide seed treatment. The survey indicated that factors such as grain price, cost of treatment, and past disease pressure influenced a grower’s decision to use a seed treatment. Past reports of common bunt experiences in conjunction with local discount schedules provide further evidence for the prevalence of common bunt in the region. To improve planting date recommendations, field experiments were conducted at three locations to evaluate the influence of weather conditions at planting on common bunt infection. Air and soil weather data were collected from soil sensors, HOBO Micro Stations, and Mesonet weather stations were used to create predictors for four fixed-length time windows around planting date. We found that planting date had a significant effect on disease incidence across locations. Generally, soil and air temperatures between 5 and 10 ℃ in the week after planting were positively associated with disease incidence ( R_m^2 = 0.42). These results have important implications for improving common bunt management in the state.
Keywords: Plant pathology; Disease management; Extension; Epidemiology; Wheat; Common bunt